Pelatihan Al-Banjari Santri TPQ Desa Kedungbogo - Sukma, Septi Ambar Indraningtia; Farrihah, Rifdatul ‘Aisyil; Rudiyanto, Nur Faiq; Darmayanti, Julia; Faizah, Nur; Ramadhani, Dewi Syafera Khoirina (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The community service program in the form of al-banjari training for TPQ santri in Kedungbogo village aims to preserve and develop traditional Islamic musical arts among the younger generation, namely al-banjari. Al-banjari is a form of tambourine musical art, which has an important role in efforts to strengthen religious and cultural values ​​in society. Usually TPQ students in Kedungbogo village use al-banjari as a herding tool during the evening Lailatus Sholawat activities. However, the lack of understanding in innovating rhythm and tone makes al-banjari activities felt less effective, and there is also a lack of trainers in carrying out al-banjari exercises. This training involves TPQ students in Kedungbogo village who have an interest in the tambourine musical art instrument. The training methods used include the caramah method and coaching. The results of the al-banjari training showed an increase in understanding of playing al-banjari using the tambourine musical instrument and by making a guidebook containing the al-banjari formula. It is hoped that the success of this training will be an inspiration for other students to be enthusiastic about preserving and developing traditional Islamic musical arts.